Answer:
a) -8
b) -56
c) 3
d) 6
Explanation:
(a). The expression is given by,
![\Rightarrow -2x^2-3x+1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/x6fvenwpqc20d9nq8gio931oir6yip9j3b.png)
Now, substitute the the value of x = 3 in the expression
![\Rightarrow -2*(-3)^2-3*(-3)+1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/qc9fbx4js4gznwas9u9e244sc0ru8nrezi.png)
![\Rightarrow -8](https://img.qammunity.org/2019/formulas/mathematics/middle-school/2nahcdb5l51ejziipstg217zvfl57kncla.png)
(b). The expression is given by,
![\Rightarrow 8-(3x-2)^2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/mvw523gapgwf65mesldr84fyt0oyd8i5zr.png)
Now, substitute the the value of x = -2 in the expression
![\Rightarrow 8-(3*(-2)-2)^2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/tm2l6e2ylk2gw5afrwhgj8k1uptuhotwx0.png)
![\Rightarrow -56](https://img.qammunity.org/2019/formulas/mathematics/middle-school/x98kme2r4qclg5lsqrp7wye1pe29h9owye.png)
(c). The expression is given by,
![\Rightarrow (-3)/(k+2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/n8fwuifit0awza6ny870b3vfqt3tbwwfy2.png)
Now, substitute the the value of k = -3 in the expression
![\Rightarrow (-3)/(-3+2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/qat85s2aj5qslmou4ur2at30luq64h1y7y.png)
![\Rightarrow 3](https://img.qammunity.org/2019/formulas/mathematics/middle-school/zbdwqlwcd7g4two748vwh7tpj4jq78o1kc.png)
(d). The expression is given by,
![\Rightarrow (15m)/(n+1)-m^2+n](https://img.qammunity.org/2019/formulas/mathematics/middle-school/gnlyt93xqdnhaexspecwcu1np5b0g5zsr7.png)
Now, substitute the the value of m = 1 and n = 2 in the expression
![\Rightarrow (15*1)/(2+1)-1^2+2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/8ujkrxzm2zlaz1yd2iow89piov7ou7o18g.png)
![\Rightarrow 6](https://img.qammunity.org/2019/formulas/mathematics/middle-school/7b2nbw8zlaa7ubux3nuv9qz2pn1zq33vqk.png)
Hence, This is the required solution.